2022
DOI: 10.1177/1934578x221143202
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Glycosides Citrulluside H and Citrulluside T Isolated From Young Watermelon (Citrullus lanatus) Fruit Have Beneficial Effects Against Cutibacterium acnes-Induced Skin Inflammation

Abstract: Acne vulgaris, typically caused by Cutibacterium acnes ( C. acnes) involves chronic inflammation of the sebaceous follicles and is the most common skin disease, afflicting 85% of adolescents. We previously isolated 2 novel phenolic glycosides, 2-caffeoyl-3-hydroxy-3-methylbutyric 4′-β-D-glucopyranosyloxy-3′-hydroxybenzyl ester (citrulluside H [CH]) and 2-caffeoyl-3-hydroxy-3-methylbutyric 4′-β-d-glucopyranosyloxybenzyl ester (citrulluside T [CT]), from young fruits of watermelon ( Citrullus lanatus). Both comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition, hydroxylamine, O-pentyl-has also been identified in the ethyl acetate extract of strain EIZ2, which showed antimicrobial activity [51]. Moreover, phenolic glycosides like butanoic acid, 3-hydroxy-3-methyl-have been associated with various biological activities, including antioxidant, antimicrobial [55], and anti-herbivore activity [90]. Furthermore, the presence of the ethanol, 2,2'-oxybis-identified in our extract has been previously documented for its diverse biological properties, including antioxidant and antimicrobial activities [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hydroxylamine, O-pentyl-has also been identified in the ethyl acetate extract of strain EIZ2, which showed antimicrobial activity [51]. Moreover, phenolic glycosides like butanoic acid, 3-hydroxy-3-methyl-have been associated with various biological activities, including antioxidant, antimicrobial [55], and anti-herbivore activity [90]. Furthermore, the presence of the ethanol, 2,2'-oxybis-identified in our extract has been previously documented for its diverse biological properties, including antioxidant and antimicrobial activities [54].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was performed with three biological and three technical replicates for each candidate gene. Cla97C05G094190 ( GAPDH ) was used as the internal control ( Itoh et al., 2023 ). The primers for qRT-PCR were designed using Primer 5 ( Lalitha, 2000 ) and are listed in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, most of the tested extracts showed low EC 50 values, which ranged between 27 and 45 µg/mL, while treatments W1-W4 and W6 recorded the lowest activity, without significant differences between them. According to Itoh et al [107], two phenolic glycosides (e.g., citrulluside H and citrulluside T) obtained from young watermelon fruit were effective against skin inflammation induced by Cutibacterium acnes. In another study, Rafi et al [108] reported that lycopene may inhibit inflammation in RAW 264.7 cell lines and suggested that fruits that are rich in lycopene could be useful as anti-inflammatory agents.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%